Comparative Analysis of the Income of Irrigated Rice Farmers and Non-Irrigated Rice Farmers in Tabir District Merangin Regency Jambi Province - Fikriman Fikriman; Firda Kartika; Isyaturriyadhah Isyaturriyadhah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This research aims to analyze the comparison of income between irrigated and non-irrigated rice farmers in Tabir District, Merangin Regency. The research location was chosen in Tabir District, Merangin Regency, with the consideration that this area has the highest harvest area, land area, and rice production in Merangin Regency. The research was conducted in December 2018. In selecting the location, a purposive approach was used. Data collection was carried out using descriptive analysis techniques, which aim to describe the current situation based on existing facts. A different t-test was used in data analysis by taking a sample of 108 respondents in Tabir District from villages that have irrigated and non-irrigated rice fields. The research results show that the income of irrigated rice farmers is IDR8,860,012.08 per planting season, while for non- irrigated rice farmers IDR5,113,529.06. Data analysis indicates that there are significant differences in income between irrigated and non-irrigated rice farmers.